PROMOSI KESEHATAN UNTUK MENINGKATKAN PENGETAHUAN DAN KETERAMPILAN IBU HAMIL DALAM PERAWATAN PAYUDARA - Destri, Yuhelva; Ristiyana, Septi; Aditia, Dita Selvia; Wahyuni, Iin (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2023)
The results of the Indonesian Demographic and Health Survey (SDKI) in 2010 showed that mothers who breastfeed their babies on the first day after giving birth are 50.2%. This shows that around 49,8% of mothers giving birth do not breastfeed their babies. From this data, as many as 63.6% of mothers gave birth experienced a slowdown in milk production on the first day (Perinasia, 2010). Breast care is very important during pregnancy until breastfeeding. This is because the breast is the only producer of breast milk which is the staple food for newborns, so it must be done as early as posibble. Where the production of breast milk will stimulate the milk glands through massage (Harahap, 2017). Breast care is very important in the third trimester so that complications do not occur when breastfeeding the baby later (Sari and Ernawati, 2016). Based on the result of a preliminary survey conducted with interviews with 20 pregnant women in Suku 3 Tiyuh Makarti, Tumijajar District, Tulang Bawang Barat Regency in 2021, as many as 18 people (80%) could not do breast care properly. This shows that only 2 (20%) pregnant women can perform breast care properly. The purpose of this community service is to provide education to pregnant women to be able to carry out breast care during pregnancy as a preparation for the breastfeeding process and to support the exclusive breastfeeding program. The community service method is carried out through lectures and demonstrations of breast care demonstration tools. The participants of the activity were 20 pregnant women. There was enthusiasm from the participants during the activity. Participants know the benefits and ways of breast care. For pregnant women to continue to apply breast care during pregnancy or after giving birth, and families to provide motivation and enthusiasm for pregnant women to do breast care.